Cardiovascular Responses, Physical Activity Intensity, and Enjoyment Level of Nintendo Switch™ Exergaming, Comparing Different Tempos and Playing Modes: A Pilot Study - Bayu Aji Mayogya Putra; Reni Hendrarati Masduchi; Martha Kurnia Kusumawardani (Faculty of Medicine, Universitas Airlangga, 2021)
Background: Physical activity (PA) has been associated with multiple health benefits. However, the global population does not meet the PA recommendations. Virtual reality exergaming (VR EXG) can become an option to increase PA because it is fun, relatively easy to access and affordable through popular commercial devices.Aim: To investigate the immediate cardiovascular responses(blood pressure, heart rate), quantification of PA intensity(percentage of maximum heart rate (%HRmax), Borg’s rating of perceived exertion (RPE), and the level of enjoyment using visual analog scale (VAS) while playing VR EXG.Material and Methods: Fifteen healthy men (aged 31.87±3.14 years old, body mass index 23.77±2.47 kg/m2) undergone three“Fitness Boxing” Nintendo Switch™ playing modes in the same order: (1) single player-normal tempo, (2) single player-fast tempo and (3) versus. During playing, participant’s HR was monitored using Polar H10 heart rate sensor. Blood pressure was measured before and after playing. Borg’s RPE and VAS were collected after playing.Results: Our results showed significant heart rate and systolic blood pressure increase (p = 0.001) in all three playing conditions, whereas diastolic blood pressure was relatively constant (p > 0.05). The Borg’s RPE were in 12-13 range (moderate) and %HRmax range between 72- 81% (vigorous). The enjoyment level was found greatest in versus mode compared to other playing modes.Conclusion: VR EXG Nintendo Switch™ “Fitness Boxing” can elicit immediate cardiovascular responses and provides an enjoyable moderate to vigorous PA intensity in healthy male adults, and can be used to meet the weekly PA recommendations.